First Observation of Transport of Solar Wind Protons Scattered From Magnetic Anomalies Into the Near Lunar Wake: Observations by SARA/Chandrayaan-1 - Dhanya, M. B.; Bhardwaj, Anil; Alok, Abhinaw; Futaana, Yoshifumi; Barabash, Stas; Wieser, Martin; Holmström, Mats; Wurz, Peter (Geophysical Research Letters, 2018)
We report the first observational evidence for the transport of the solar wind protons scattered from the lunar magnetic anomaly (LMA) into the near wake region from SWIM/Sub‐keV Atom Reflecting Analyzer (SARA) aboard Chandrayaan‐1. These protons with high angular spread are observed in the near wake region for specific orientations of interplanetary magnetic field. The typical energy range is 600–1,000 eV, which is either smaller or comparable to that of solar wind. Using our backtracing model, the source region of these protons is found to be the large LMA at South Pole‐Aitken basin on the dayside, suggesting that these are solar wind protons forward scattered from LMA at the South Pole‐Aitken. The flux of these protons is ~5 × 10⁻⁴ of the solar wind proton flux, which is comparable to the proton population in near wake due to other known processes. Such protons can significantly affect the electromagnetic environment in near wake region.